Transforming towards a high income People Republic of China challenges and recommendations. (Metro Manila, Philippines Asian Development Bank, 2017)
The People Republic of China PRC has experienced stellar economic performance over the last 3 decades. Gross domestic product growth has averaged 10% per year. Per capita income has increased by a factor of 13. Life expectancy at birth increased from 67 to 73 years. Rapid growth, however, has posed eight challenges for the PRC industrial transformation, balanced rural urban development, human resource transformation, environmental protection, climate change mitigation, water security, subnational debt management, and further integration with the international economic system. In 2013, ADB was invited to provide inputs to support the preparation of the 13th Five Year Plan 20162020. This report summarizes key issues and recommends practical policy options to address the PRCs challenges.
Keywords: Economic development projects; Sustainable development -- Economic aspects; Electronic books